The War for America's Natural Resources - Nester, William R. author. aut Link
VII, 256 p.
Keywords: Throughout most of American history, natural resource policies reflected the dominant philosophy of cornucopianism. As conservationism and environmentalism arose to struggle with cornucopianism for mass public acceptance, so too did the policies that flowed from those respective philosophies. The result has increasingly been a range of federal policies which reflect aspects of all three conflicting philosophies. The War for America's Natural Resources analyzes the dynamic among natural resource politics, policies and philosophies. Each chapter explores in-depth the development of policies toward America's soil, wildlife, water, energy, grasslands, minerals, forests and air.